The Early Detection Tool for Bladder Cancer Based on Quantum Dots Fluorescence Integrated with Fuzzy Logic Classification Application Programming Interface - Ekiawan, Krisna Seiya; Tan, Evan Manuel; Faustin, Levina Nasywa; Ahmad, Verousson; Suroso, Ajeng Lintang Kinasih; Budaya, Taufiq Nur; Nurussa’adah, Nurussa’adah (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
Cancer is a disease caused by genetic changes that cause abnormal and uncontrolled cell growth. One of the cancers with an enormous growth in the number of cases is bladder cancer, with the number of new cases in 2020 amounting to 573,000 cases in the world. This number is supported by inadequate early detection modalities that cannot reach the wider community. The Detection On The Spot Bladder Cancer (DOTS Bca) innovation aims to reduce the prevalence of bladder cancer and becomes an affordable early bladder cancer detection tool that can be used repeatedly and has high sensitivity. DOTS BCa detects the 47 kiloDalton epitope protein biomarker in the patient's urine. This tool uses Carbon Quantum Dots (CDs) as a semiconductor material, which will be analyzed for the level of fluorescence when it binds to a 47 kiloDalton epitope. The innovation design method includes literature study, design, tool making and testing. The early detection system test was carried out by comparing the CDs fluorescence results with the bladder cancer diagnostic test and obtained an accuracy of 85% with sensitivity 90% and specificity 80%. This tool is analyzed using fluorescence resonance energy transfer, integrated application programming interface, and fuzzy logic classification, which can work non-invasively.